Chemical solution for SMT printing template etching, preparation method and application thereof
By using chemical solutions of specific compositions, including ferric chloride, sodium chloride, copper chloride and composite etching protectors, the surface matte and hydrophobic effects of SMT printing templates after etching are achieved, solving the problems of large surface roughness and uncontrollable morphological quality in the prior art, and improving the etching quality and repeatability.
Patent Information
- Application Number
- CN202411254182.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing chemical solutions for etching SMT printing templates have too large surface roughness after etching, the etching morphology quality is uncontrollable, and the repeatability is poor, which cannot meet the accuracy requirements and quality expectations of SMT printing templates.
A chemical solution composed of solution A formed by mixing ferric chloride and hydrochloric acid, solution B formed by mixing sodium chloride and copper chloride and a composite etching protecting agent, through a specific volume ratio and solid-liquid ratio, combined with hydrolysis and mixing of components such as fluorosilane FT-922, is used to form an etching solution with regular and orderly chemical reactions.
Through the regular and orderly chemical reactions of copper and ferric chloride generated and deposited, excessive corrosion of ferric chloride on the surface of the template is inhibited, forming a matte surface and improving hydrophobic properties, significantly improving etching quality and repeatability.
Smart Images

Figure CN119121234B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of etching solution technology, and in particular to a chemical solution for SMT printing template etching, a preparation method thereof, and an application thereof. Background Art
[0002] Surface mount technology refers to the assembly technology that directly solders surface mount components SMC / SMD to the specified position on the surface of the PCB without inserting holes on the printed circuit board PCB. It is also called surface mounting technology or surface assembly technology, referred to as SMT. SMT printing template, also known as leak plate or steel mesh, is a flat mold used in the process of leaking solder paste or dispensing glue. The solder palace or glue printing in the SMT process first used screen printing, and was later gradually replaced by metal (copper, stainless steel, high-strength polyester) templates. Its manufacturing methods include chemical corrosion, electrochemical forming, and laser cutting.
[0003] With the increasingly sophisticated production of electronic products and the rapid development and progress of chip packaging technology, the requirements and indicators of SMT processes are also moving towards more and more precision. In this process, the increasingly sophisticated process parameters have put forward higher precision requirements and quality expectations for SMT printing templates.
[0004] Related technology can refer to the Chinese invention application with publication number CN102061476A, which provides an etching solution for carbon steel and low alloy steel, comprising the following components in weight ratios: 80 to 100 parts of CuSO4, 15 to 25 parts of AgNO3, 10 to 30 parts of Ni(NO3)2, 3 to 12 parts of selenium, 20 to 40 parts of 65% HNO3, and 90 to 110 parts of water.
[0005] Regarding the above-mentioned related technologies, although the etching solution has strong etching ability and high etching rate, it has problems such as excessive roughness of the template surface after etching, uncontrollable etching morphology quality, and poor etching repeatability, which cannot meet the accuracy requirements and quality expectations of SMT printing templates. Summary of the invention
[0006] In order to solve the problem that the surface roughness of the template after etching is too large and the quality of the etching morphology is uncontrollable, the present application provides a chemical solution for SMT printing template etching, a preparation method and application thereof.
[0007] The chemical solution for SMT printing template etching provided by the present application adopts the following technical solution:
[0008] The chemical solution for SMT printing template etching comprises raw materials including solution A formed by mixing ferric chloride and hydrochloric acid solution, solution B formed by mixing sodium chloride and cupric chloride solution, and a composite etching protective agent; the volume ratio of solution A, solution B, and composite etching protective agent is 4-6:1:0.01-0.05; the solid-liquid ratio of sodium chloride to cupric chloride solution is 50-60:1 g / L; the composite etching protective agent comprises fluorosilane FT-922, nonylphenol polyoxyethylene ether NP-10, sodium silicate, deionized water, and ethanol, and the mass ratio is 4.5-5:0.045-0.05:0.23-0.25:6.75-7.5:101.25-112.5.
[0009] By adopting the above technical solution, the iron element at the position to be etched in the SMT printing template material undergoes a regular and orderly chemical reaction with the ferric chloride and cupric chloride in the chemical solution at the same time:
[0010] 2FeCl3+Fe=3FeCl2;
[0011] CuCl2+Fe=FeCl2+Cu;
[0012] The above chemical reaction generates copper (Cu) that is uniformly deposited on the template surface, and at the same time continues to react chemically with the ferric chloride in the circulating spray solution:
[0013] 2FeCl3+Cu=CuCl2+2FeCl2;
[0014] It is precisely because the metallic copper generated and deposited on the template material in the above chemical reaction process can react chemically with the ferric chloride in the solution at the same time, which can inhibit the excessive corrosion of the template surface by the ferric chloride component to a certain extent, and avoid the uncontrollable state of the template surface roughness and the hydrophobic state of the surface structure after etching;
[0015] The above-mentioned continuous chemical reactions can cause local corrosion and thinning of the material surface, while forming a matte surface with specific hydrophobic properties.
[0016] At the same time, the present application adds a composite etching protectant during the etching process. After the hydrolysis of fluorosilane FT-922, Si-OH groups are formed, which can form a layer of low surface energy, super-hydrophobic protective film on the iron surface, slowing down the etching rate and effectively improving the etching quality.
[0017] Preferably, the specific gravity of solution A is 1.38-1.40.
[0018] Preferably, the hydrochloric acid solution consists of industrial hydrochloric acid and deionized water; the volume ratio of the industrial hydrochloric acid to the deionized water is 1:4-5.
[0019] Preferably, the cupric chloride solution consists of cupric chloride and deionized water; the specific gravity of the cupric chloride solution is 1.32-1.35.
[0020] The present application also provides a method for preparing a chemical solution for SMT printing template etching, using the following technical solution:
[0021] The method for preparing a chemical solution for precision etching of an SMT printing template comprises the following steps:
[0022] S1. Add ferric chloride to the hydrochloric acid solution to obtain solution A;
[0023] S2. adding sodium chloride to the copper chloride solution to obtain solution B;
[0024] S3. The fluorosilane FT-922, distilled water and anhydrous ethanol were mixed and ultrasonically dispersed for 30-45 min, and then removed and magnetically stirred for 5-7 h to fully hydrolyze; nonylphenol polyoxyethylene ether NP-10 and sodium silicate were added and stirred evenly to obtain a composite etching protective agent;
[0025] S4. Mix solution A, solution B, and the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0026] The present application also provides an application of a chemical solution for SMT printing template etching, using the following technical solution:
[0027] Application of chemical solution for precise etching of SMT printing template, application of the chemical solution in local precise etching of SMT printing template.
[0028] Preferably, the material of the SMT printing template is one of 304 stainless steel, 301 stainless steel, and nickel-iron alloy.
[0029] Preferably, the thickness of the SMT printing template is ≥0.02 mm.
[0030] Preferably, the working temperature of the chemical solution during local precision etching is 48-52°C.
[0031] In summary, the present application includes at least one of the following beneficial technical effects:
[0032] 1. The iron element at the position to be etched in the SMT printing template material reacts with the ferric chloride and cupric chloride in the chemical solution in a regular and orderly manner. The metallic copper generated and deposited on the template material during the chemical reaction can react with the ferric chloride in the solution at the same time, which can inhibit the excessive corrosion of the template surface by the ferric chloride component to a certain extent, and avoid the uncontrollable state of the template surface roughness and the hydrophobic state of the surface structure after etching;
[0033] 2. Through the ratio of A and B solutions in the chemical solution, combined with the appropriate working temperature conditions for the solution, a precision etching solution for etching a template with a matte surface and good hydrophobic properties is obtained;
[0034] 3. The present application adds a composite etching protective agent during the etching process. After the hydrolysis of fluorosilane FT-922, Si-OH groups are formed, which can form a low surface energy, super-hydrophobic protective film on the iron surface, slowing down the etching rate and effectively improving the etching quality.
[0035] 4. The etched template surface has excellent hydrophobic and anti-fouling properties; it achieves no flux or solder paste residue after template printing, thus achieving the excellent performance of continuous printing and cleaning-free printing of the printed template, which has significant competitive advantages compared with the products of peer manufacturers. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a surface etching quality inspection diagram of Application Example 1 of this application.
[0037] Figure 2 This is the surface etching quality inspection diagram of comparative application example 3 of this application. DETAILED DESCRIPTION
[0038] The present application is further described in detail below in conjunction with embodiments and drawings.
[0039] Example 1
[0040] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0041] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0042] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0043] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0044] Example 2
[0045] S1. 100 mL of industrial hydrochloric acid and 450 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0046] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0047] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0048] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0049] Example 3
[0050] S1. 100 mL of industrial hydrochloric acid and 500 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0051] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0052] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0053] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0054] Example 4
[0055] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.39;
[0056] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0057] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0058] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0059] Example 5
[0060] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.40;
[0061] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0062] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0063] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0064] Example 6
[0065] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.36;
[0066] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0067] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0068] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0069] Example 7
[0070] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.42;
[0071] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0072] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0073] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0074] Example 8
[0075] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0076] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.34, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0077] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0078] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0079] Example 9
[0080] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0081] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.35, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0082] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0083] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0084] Example 10
[0085] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0086] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.30, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0087] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0088] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0089] Embodiment 11
[0090] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0091] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.37, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0092] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0093] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0094] Example 12
[0095] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0096] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5.5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0097] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0098] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0099] Example 13
[0100] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0101] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 6 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0102] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0103] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0104] Embodiment 14
[0105] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0106] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0107] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0108] S4. Mix 500 mL of solution A, 100 mL of solution B, and 3 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0109] Embodiment 15
[0110] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0111] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0112] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0113] S4. Mix 600 mL of solution A, 100 mL of solution B, and 5 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0114] Example 16
[0115] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0116] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0117] S3. Weigh 4.5g of fluorosilane FT-922, 0.045g of nonylphenol polyoxyethylene ether NP-10, 0.23g of sodium silicate, 6.75g of deionized water, and 101.25g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30 minutes, then take them out and stir them magnetically for 5 hours to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0118] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0119] Embodiment 17
[0120] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0121] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0122] S3. Weigh 5g of fluorosilane FT-922, 0.05g of nonylphenol polyoxyethylene ether NP-10, 0.25g of sodium silicate, 7.5g of deionized water, and 112.5g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30 minutes, then take them out and stir them magnetically for 5 hours to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0123] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0124] Comparative Example
[0125] Comparative Example 1
[0126] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0127] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0128] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0129] S4. Mix 300 mL of solution A, 100 mL of solution B, and 0.1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0130] Comparative Example 2
[0131] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0132] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0133] S3. Weigh 4g of fluorosilane FT-922, 0.04g of nonylphenol polyoxyethylene ether NP-10, 0.2g of sodium silicate, 6g of deionized water, and 90g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30min, then take them out and stir them magnetically for 5h to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0134] S4. Mix 700 mL of solution A, 100 mL of solution B, and 8 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0135] Comparative Example 3
[0136] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0137] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0138] S3. Mix 400 mL of solution A and 100 mL of solution B, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0139] Comparative Example 4
[0140] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0141] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0142] S3. Weigh 3g of fluorosilane FT-922, 0.02g of nonylphenol polyoxyethylene ether NP-10, 0.1g of sodium silicate, 5g of deionized water, and 80g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30 minutes, then take them out and stir them magnetically for 5 hours to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0143] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0144] Comparative Example 5
[0145] S1. 100 mL of industrial hydrochloric acid and 400 mL of deionized water were mixed to obtain a hydrochloric acid solution; an appropriate amount of ferric chloride was added to the hydrochloric acid solution until mixed uniformly to obtain a solution A having a specific gravity of 1.38;
[0146] S2. The copper chloride was prepared with deionized water into a copper chloride solution with a specific gravity of 1.32, 100 mL of the copper chloride solution was then added with 5 g of industrial grade sodium chloride, and the mixture was mixed to obtain a solution B;
[0147] S3. Weigh 6g of fluorosilane FT-922, 0.06g of nonylphenol polyoxyethylene ether NP-10, 0.3g of sodium silicate, 8g of deionized water, and 120g of ethanol; mix fluorosilane FT-922, distilled water, and anhydrous ethanol and disperse them ultrasonically for 30 minutes, then take them out and stir them magnetically for 5 hours to fully hydrolyze them; add nonylphenol polyoxyethylene ether NP-10 and sodium silicate and stir evenly to obtain a composite etching protective agent;
[0148] S4. Mix 400 mL of solution A, 100 mL of solution B, and 1 mL of the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
[0149] Application Examples
[0150] Application Example 1
[0151] The chemical solution for SMT printing template etching obtained in Example 1 was used to perform local precision thinning on a 304 stainless steel template of 5×4 cm and 0.02 mm in thickness under conventional horizontal etching process conditions, and the etching working temperature was controlled to be 48°C.
[0152] Application Example 2
[0153] The chemical solution for SMT printing template etching obtained in Example 1 was used to perform local precision thinning on a 301 stainless steel template of 5×4 cm and 0.05 mm in thickness under conventional horizontal etching process conditions, and the etching working temperature was controlled to be 48°C.
[0154] Application Example 3
[0155] The chemical solution for SMT printing template etching obtained in Example 1 was used to perform local precise thinning on a nickel-iron alloy template of 5×4 cm and 0.1 mm in thickness under conventional horizontal etching process conditions, and the etching working temperature was controlled to be 48°C.
[0156] Application Example 4
[0157] The chemical solution for SMT printing template etching obtained in Example 1 was used to perform local precision thinning on a 304 stainless steel template of 5×4 cm and 0.02 mm in thickness under conventional horizontal etching process conditions, and the etching working temperature was controlled to be 50° C.
[0158] Application Example 5
[0159] The chemical solution for SMT printing template etching obtained in Example 1 was used to perform local precision thinning on a 304 stainless steel template of 5×4 cm and 0.02 mm in thickness under conventional horizontal etching process conditions, and the etching working temperature was controlled to be 52° C.
[0160] Application Example 6
[0161] The chemical solution for SMT printing template etching obtained in Example 1 was used to perform local precision thinning on a 304 stainless steel template of 5×4 cm and 0.02 mm in thickness under conventional horizontal etching process conditions, and the etching working temperature was controlled to be 40°C.
[0162] Application Example 7
[0163] The chemical solution for SMT printing template etching obtained in Example 1 was used to perform local precision thinning on a 304 stainless steel template of 5×4 cm and 0.02 mm in thickness under conventional horizontal etching process conditions, and the etching working temperature was controlled to be 60°C.
[0164] Application Example 8
[0165] The difference between Application Example 8 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 8 comes from Example 2.
[0166] Application Example 9
[0167] The difference between Application Example 9 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 9 comes from Example 3.
[0168] Application Example 10
[0169] The difference between Application Example 10 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 10 comes from Example 4.
[0170] Application Example 11
[0171] The difference between Application Example 11 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 11 comes from Example 5.
[0172] Application Example 12
[0173] The difference between Application Example 12 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 12 comes from Example 6.
[0174] Application Example 13
[0175] The difference between Application Example 13 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 13 comes from Example 7.
[0176] Application Example 14
[0177] The difference between Application Example 14 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 14 comes from Example 8.
[0178] Application Example 15
[0179] The difference between Application Example 15 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 15 comes from Example 9.
[0180] Application Example 16
[0181] The difference between Application Example 16 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 16 comes from Example 10.
[0182] Application Example 17
[0183] The difference between Application Example 17 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 17 comes from Example 11.
[0184] Application Example 18
[0185] The difference between Application Example 18 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 18 comes from Example 12.
[0186] Application Example 19
[0187] The difference between Application Example 19 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 19 comes from Example 13.
[0188] Application Example 20
[0189] The difference between Application Example 20 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 20 comes from Example 14.
[0190] Application Example 21
[0191] The difference between Application Example 21 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 21 comes from Example 15.
[0192] Application Example 22
[0193] The difference between Application Example 22 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 22 comes from Example 16.
[0194] Application Example 23
[0195] The difference between Application Example 23 and Application Example 1 is that the chemical solution used for SMT printing template etching in Application Example 23 comes from Example 17.
[0196] Comparative Application Examples
[0197] Comparative application example 1
[0198] The difference between Comparative Application Example 1 and Application Example 1 is that the chemical solution used for SMT printing template etching in Comparative Application Example 1 comes from Comparative Example 1.
[0199] Comparative Application Example 2
[0200] The difference between Comparative Application Example 2 and Application Example 1 is that the chemical solution used for SMT printing template etching in Comparative Application Example 2 comes from Comparative Example 2.
[0201] Comparative Application Example 3
[0202] The difference between Comparative Application Example 3 and Application Example 1 is that the chemical solution used for SMT printing template etching in Comparative Application Example 3 comes from Comparative Example 3.
[0203] Comparative Application Example 4
[0204] The difference between Comparative Application Example 4 and Application Example 1 is that the chemical solution used for SMT printing template etching in Comparative Application Example 4 comes from Comparative Example 4.
[0205] Comparative Application Example 5
[0206] The difference between Comparative Application Example 5 and Application Example 1 is that the chemical solution used for SMT printing template etching in Comparative Application Example 5 comes from Comparative Example 5.
[0207] Performance testing
[0208] The etching rates, etching resistance time and etching quality of the above-mentioned application examples 1-21 and comparative application examples 1-4 were tested, and the results are shown in Table 1.
[0209] The specific test results are as follows:
[0210] Table 1 Performance test results
[0211] Detection object Etching rate / (μm / min) Anti-corrosion time Etching quality Application Example 1 8.3 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 2 7.4 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 3 7.8 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 4 8.6 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 5 8.5 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 6 6.7 <72h The surface is rough and not hydrophobic Application Example 7 6.9 <72h The surface is rough and not hydrophobic Application Example 8 8.5 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 9 8.4 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 10 8.8 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 11 8.4 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 12 6.6 >72h The surface is rough and not hydrophobic Application Example 13 7.0 >72h The surface is rough, the structure is uneven, and the hydrophobic and antifouling properties are poor Application Example 14 8.5 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 15 8.2 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 16 7.2 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 17 6.6 <72h The surface is rough and not hydrophobic Application Example 18 8.3 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 19 8.3 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 20 9.1 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 21 8.5 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 22 8.5 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Application Example 23 8.0 >72h Matt surface, uniform structure, good hydrophobic and antifouling properties Comparative application example 1 4.5 <72h The surface is rough and not hydrophobic Comparative Application Example 2 4.7 <72h The surface is rough and not hydrophobic Comparative Application Example 3 1.0 <72h The surface is rough and not hydrophobic Comparative Application Example 4 5.7 <72h The surface is rough and not hydrophobic Comparative Application Example 5 5.4 <72h The surface is rough and not hydrophobic
[0212] It can be seen from the test results in Table 1 that the chemical solution for precision etching of SMT printing templates provided by the present application can perform local precision thinning treatment on precision templates with a thickness of 0.020 mm, causing the surface of the material to be locally corroded and thinned, while forming the characteristics of matte surface and uniform structure of the material. The etched template surface has excellent hydrophobic and anti-fouling properties, such as Figure 1 As shown, it can be achieved that there is no flux or solder paste residue after template printing, thereby achieving the excellent performance of continuous printing and cleaning-free printing of the printing template.
[0213] It can be seen from the test results of Application Examples 1, 4, 5, 6, and 7 that the etching solution provided in the present application has an optimal working temperature of 48-52°C. Working temperatures below or above this temperature range can easily lead to excessive roughness of the template surface after etching, and a surface structure state with hydrophobic properties cannot be formed.
[0214] It can be seen from the test results of comparative application example 3 that when the etching solution provided by the present application is not added with a composite etching protective agent, the surface roughness of the template after etching is too large and a surface structure state with hydrophobic characteristics cannot be formed, such as Figure 2 As shown. It can be seen from the test results of comparative application examples 4 and 5 that the composite etching protective agent provided by the present application preferably has a mass ratio of fluorosilane FT-922, nonylphenol polyoxyethylene ether NP-10, sodium silicate, deionized water, and ethanol of 4-5: 0.04-0.05: 0.2-0.25: 6-7.5: 90-112.5. A ratio lower than or higher than this range is likely to cause the surface roughness of the template after etching to be too large, and a surface structure state with hydrophobic characteristics cannot be formed.
[0215] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. Chemical solution for SMT printing template etching, characterized by: The raw materials include solution A formed by mixing ferric chloride and hydrochloric acid solution, solution B formed by mixing sodium chloride and cupric chloride solution, and a composite etching protective agent; the volume ratio of solution A, solution B, and composite etching protective agent is 4-6:1:0.01-0.05; the solid-liquid ratio of sodium chloride to cupric chloride solution is 50-60:1 g / L; the composite etching protective agent includes fluorosilane FT-922, nonylphenol polyoxyethylene ether NP-10, sodium silicate, deionized water, and ethanol, and the mass ratio is 4.5-5:0.045-0.05:0.23-0.25:6.75-7.5:101.25-112.5; The specific gravity of the solution A is 1.38-1.40; The cupric chloride solution consists of cupric chloride and deionized water; the specific gravity of the cupric chloride solution is 1.32-1.
35.
2. The chemical solution for SMT printing template etching according to claim 1, characterized in that: The hydrochloric acid solution consists of industrial hydrochloric acid and deionized water; the volume ratio of the industrial hydrochloric acid to the deionized water is 1:4-5.
3. The method for preparing a chemical solution for SMT printing template etching according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Industrial hydrochloric acid and deionized water are configured in a volume ratio of 1:4-5 to obtain a hydrochloric acid solution; Adding ferric chloride to the hydrochloric acid solution to obtain solution A; S2. adding sodium chloride to the copper chloride solution to obtain solution B; S3. The fluorosilane FT-922, deionized water and anhydrous ethanol were mixed and ultrasonically dispersed for 30-45 min, and then removed and magnetically stirred for 5-7 h to fully hydrolyze; nonylphenol polyoxyethylene ether NP-10 and sodium silicate were added and stirred evenly to obtain a composite etching protective agent; S4. Mix solution A, solution B, and the composite etching protective agent, stir evenly, and obtain a chemical solution for SMT printing template etching.
4. The use of the chemical solution for SMT printing template etching according to any one of claims 1-2, characterized in that: The chemical solution is used in local or overall precise etching of an SMT printing template; the working temperature of the chemical solution during local precise etching is 48-52°C.
5. The use of the chemical solution for SMT printing template etching according to claim 4, characterized in that: The material of the SMT printing template is one of 304 stainless steel, 301 stainless steel, and nickel-iron alloy.
6. The use of the chemical solution for SMT printing template etching according to claim 4, characterized in that: The thickness of the SMT printing template is ≥0.02 mm.
Citation Information
Patent Citations
Etching liquid for carbon steel and low alloy steel
CN102061476A
Corrosive for displaying billet rimholes and preparation method thereof
CN103471900A
Surface treatment liquid for 3D printed stainless steel parts and surface treatment device
CN109097778A